Pernikahan Beda Agama - Ikram, Muhammad Furqanul; Shuhufi, Muhammad; M, Misbahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Interfaith marriages are a phenomenon that is increasingly occurring in the era of globalization and modernization. An increasingly diverse and open society, coupled with easy access to information and human mobility, has made cross-cultural and religious interactions commonplace. In the Indonesian context, which has a variety of religions and beliefs, interfaith marriage is a quite complex and sensitive issue. The main topic in this discussion is interfaith marriages carried out by Muslim men or women with non-Muslim men or women, which are then formulated into several problem formulations, namely: (1) What is the law on interfaith marriages in Islamic law?; (2) What are the impacts that arise if an interfaith marriage occurs?; (3) What are examples of cases of interfaith marriages in Indonesia.